Development of the Family Togetherness Scale: A Mixed-Methods Validation Study in Kenya - Puffer, Eve S.; Giusto, Ali; Rieder, Amber D.; Friis-Healy, Elsa; Ayuku, David; Green, Eric P. (Frontiers in Psychology, 2021)
Family functioning is an important target of clinical intervention and research given its close ties with mental health outcomes of both children and adults. However, we lack family functioning measures validated for use in many low- and middle-income country (LMIC) settings. In this mixed-methods prospective diagnostic accuracy study, we first used formative qualitative data to develop an extensive battery of screening items to measure family functioning in Kenya. We then recruited 30 Kenyan families (N = 44 adults; 30 youth aged 8-17 years) to complete the questionnaires and participate in clinical interviews conducted by local interviewers. Quantitative and qualitative analyses were then conducted to select a subset of screening items that balanced conceptual understanding of family distress with diagnostic efficiency and accuracy to yield a brief but valid scale. The final index test consisting of 30 items correctly identified distressed families in 89% of cases according to adult-report and 76% of cases according to child-report. The optimal cutoffs are associated with estimates of sensitivity/specificity of 0.88/0.90 and 0.75/0.77 for adult-report and child-report measures, respectively. The final measure—the Family Togetherness Scale—assesses global family functioning, including items related to family organization, emotional closeness, and communication/problem-solving. In addition to general items, the scale also includes items explicitly assessing family responses to stressors common in LMIC settings. Results establish a strong rationale for larger-scale validation studies.